2017
DOI: 10.14336/ad.2016.1230
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and Aging - the Inflammatory Connection

Abstract: Aging and cancer are highly correlated biological phenomena. Various cellular processes such as DNA damage responses and cellular senescence that serve as tumor suppressing mechanisms throughout life result in degenerative changes and contribute to the aging phenotype. In turn, aging is considered a pro-tumorigenic state, and constitutes the single most important risk factor for cancer development. However, the causative relations between aging and cancer is not straight forward, as these processes carry contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
86
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 185 publications
0
86
0
2
Order By: Relevance
“…Aging could markedly increase the probability to develop invasive cancers, especially for prostate cancer in men, breast cancer in women, lung and colorectal cancer in both sexes . Aging and cancer are highly correlated biological phenomena, but their causative relation is not straightforward and still under extensive studies . Although much effort was made to study why aging causes cancer, less attention was paid to the unique features of cancer in elderly patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging could markedly increase the probability to develop invasive cancers, especially for prostate cancer in men, breast cancer in women, lung and colorectal cancer in both sexes . Aging and cancer are highly correlated biological phenomena, but their causative relation is not straightforward and still under extensive studies . Although much effort was made to study why aging causes cancer, less attention was paid to the unique features of cancer in elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…1 Aging and cancer are highly correlated biological phenomena, but their causative relation is not straightforward and still under extensive studies. 2,3 Although much effort was made to study why aging causes cancer, less attention was paid to the unique features of cancer in elderly patients. Several previous studies have revealed some transcriptomics signatures of aging in different tissues.…”
Section: Introductionmentioning
confidence: 99%
“…High levels of inflammation in tumor-bearing mice can increase vascular permeability, and tumor tissues also secrete many factors to induce the destruction of vascular endothelial integrity [31,32]. Along with the deterioration of other tissues during the aging process, immune system function declines as well [33]. Hence, immune surveillance is a key factor in preventing cancer progression, and immunosenescence is another important factor that links tumorigenesis and aging [34].…”
Section: Discussionmentioning
confidence: 99%
“…Age-related changes to immune system function, often referred to as immunosenescence [17][18][19][20], are generally thought of as immune insufficiency, such as reduced anti-infection and vaccine immunity [21] and reduced tumor surveillance [22,23]. However, self-reactive immune responses are elevated in the elderly, which is a result of inflammaging, a chronic, low-grade, systemic inflammatory phenotype in the absence of acute infection observed in aged individuals [24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%